Ecotourism : the TOP 50 sustainable destinations to travel green - Stendardi, Maddalena, ....- (Milan : White Star, 2020)
Developed in the late 80's, the eco-tourist approach is characterized by a twofold concern for the places visited and the well-being of the people who live there. The means of eco-sustainable transport can be diverse: a canoe or kayak, a bicycle, a horse or mule... even our own legs!
Keywords: Duurzaam toerisme